Proficiency, attitudes and practices of university students as regards smoking electronic cigarettes (Research, Society and Development, 2024)
Objectives: This research was created as a review on the topic and conducted research among university students, by using a questionnaire to assess the use of EC’s and knowledge of risks and oral changes caused by them. Materials and Methods: A review was made on the topic, searched in the Medline and Latindex databases, period from 2011 to 2023. An exploratory and cross-sectional research was made by collecting data obtained with use of a semi-structured Google Forms questionnaire. Results: In total 486 responses were obtained, with 114 (23.46%) respondents declaring they were smokers and 83 users of EC; 92.77% used nicotine; 7.22% recognized the EC as being the “door of entry” to smoking CC; 49.4% had never smoked before using these devices; and 26.5% declared that the EC was a strategy to reduce the use of CC. The most frequently declared effects related to EC use were yellow-brown staining of teeth (35.53%), absence of saliva (30.12%) and ulcers (22.51%); 54.22% of the users had never searched information regarding the effects on oral health. Conclusions: The results demonstrate the need to expand information among the population, particularly young people, with the purpose of preventing an increase in the use of EC.